Noncoherent receivers for multichip differentially encoded DS-CDMA. - Schober, R.
We design and analyze novel noncoherent receivers for direct-sequence code-division multiple access (DS-CDMA) with multi-chip (MC) differential encoding (DE). The proposed receivers for MC-DE are based on multiple-symbol detection and decision-feedback differential detection, which have been previously applied for symbol-level DE. While the complexity of the proposed receivers is moderate, it is shown that they enable large performance gains over conventional differential detection for various channel environments, such as additive white Gaussian noise (AGWN) channels, Rayleigh and Ricean fading channels, and channels with frequency offset and phase noise. Furthermore, we show that in most cases MC-DE outperforms single-chip differential encoding and, in addition, decreases receiver complexity. Another result of this paper is that quaternary differential phase-shift keying (QDPSK) is more suitable for chip-level DE than binary DPSK.
Keywords: Rayleigh fading channel; Ricean fading channel; Additive white Gaussian noise channel; Computational complexity; Decision-feedback differential detection; Differential encoding; Direct-sequence code-division multiple access; Frequency offset; Multichip differentially encoded DS-CDMA.; Multiple-symbol detection; Noncoherent receiver; Phase noise; Quaternary differential phase-shift keying; Time-variant channel